The Role of Knowledge, Skills and Experiences of SMEs in Poverty Reduction - Imam Baidlowi; Waspodo Tjipto Subroto (Dinamika Pendidikan, 2024)
The success of an entity needs knowledge, skills, and experiences in business. For instance, knowledge on Small and Medium Enterprises (SMEs), skills, and experiences in business is a vital component in poverty reduction. The purpose of this study therefore was to determine the role knowledge of SMEs, skills and experiences in business activities in poverty reduction.  The respondents were 370 business people from 37 counties and cities in East Java. Their selection was based on cluster purposive sampling technique, and Structural Equation Modelling and regression two-stage were used for data analysis. The study established that knowledge has a significant influence impact on business but does not on influence poverty reduction. Also, skills in SMEs have a significant impact in poverty reduction. The experiences in business have are influence and significant impact at profitabilities and poverty reduction. Generally, knowledge, skill, and experiences on SMEs have a significant impact on reducing poverty.